PREDICTION STUDY OF FACTORS INFLUENCING PAIN COPING STRATEGIES OF PATIENTS WITH CERVICAL CANCER - Muchlisin, Muchlisin; Handayani, Fitria; Kusumaningrum, Niken Safitri Dyan (Jurnal Keperawatan Respati Yogyakarta, 2021)
Pain is an issue often experienced by cervical cancer patients. Some coping strategies to manage this issue have been conducted by patients. However, its success is influenced by some factors. This study aimed to predict factors influencing coping strategy of pain among cervical cancer patients. The Method is a correlational analytic study had involved cervical cancer patients staged 2 and 3 aged 25 – 65 years old with pain and chemotherapy. The Coping Strategies Questionnaire (CSQ) was used to assess coping strategy describing patient’s thought and feeling associated with pain. Multivariate regression analysis was used to analyse data. The result is Out of 92 respondents, 50% were categorised as late adulthood and 59.8% experience mild pain. Result showed that coping strategy is associated with education, age, marital state, leucocyte and pain scale (p value < 0.05). However, occupation, income, chemotherapy cycle, chemotherapy effects, haemoglobin, thrombocyte, urea and creatinine are not significantly related to coping strategy. Besides, multivariate regression analysis shows that the most influencing factor toward coping strategy is the variable of age. Age is the most influencing factor toward individual’s coping. For that reason, strengthening coping strategy of cervical cancer patients needs to maintain age factor. Keywords: Cervical Cancer; Pain Coping; Coping Strategy